2021
DOI: 10.1093/mtomcs/mfab042
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mitochondrial apoptosis pathway mediated through caspase-8 and c-Jun N-terminal kinase by cadmium-activated Fas in rat cortical neurons

Abstract: Cadmium (Cd) is a toxic metal and an environmental pollutant, and can cause neurotoxicity by inducing apoptosis. Fas (CD95/Apo-1) is a cell surface receptor that triggers apoptosis upon ligand binding, mediated through the mitochondrial apoptotic pathway. However, the role and regulatory mechanism of Fas in Cd-induced neuronal apoptosis remains understudied. Here, we demonstrate that activation of caspase-8 and the JNK pathway are mechanisms underlying Cd-induced Fas-mediated activation of the mitochondrial ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…59 Cadmium also increases ROS levels and activates caspase-8 to damage mitochondrial. 60,61 The dysfunction of mitochondria causes the release of apoptogenic factors including cytochrome c from mitochondria, resulting in the activation of caspase-3. 62 Assessment of apoptogenic factors such as cytochrome c, cytosolic calcium levels as well as the activity of other caspases can help to elucidate the exact mechanism(s) involved in the apoptosis of human lymphocytes treated with cadmium.
Figure 5.Possible mechanisms involved in cadmium-induced apoptosis in human lymphocytes.
…”
Section: Discussionmentioning
confidence: 99%
“…59 Cadmium also increases ROS levels and activates caspase-8 to damage mitochondrial. 60,61 The dysfunction of mitochondria causes the release of apoptogenic factors including cytochrome c from mitochondria, resulting in the activation of caspase-3. 62 Assessment of apoptogenic factors such as cytochrome c, cytosolic calcium levels as well as the activity of other caspases can help to elucidate the exact mechanism(s) involved in the apoptosis of human lymphocytes treated with cadmium.
Figure 5.Possible mechanisms involved in cadmium-induced apoptosis in human lymphocytes.
…”
Section: Discussionmentioning
confidence: 99%
“…According to research, more apoptotic sperm was reported in the semen of infertile patients than in fertile donors [ 18 ]. The most significant characteristics of apoptosis are activation of caspase, chromatin condensation, DNA fragmentation, changes in phosphatidylserine location within the plasma membrane, and disturbance of mitochondrial membrane potential (MMP) [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that Cd can activate the Fas/FasL‐mediated mitochondrial apoptotic pathway in PC12 cells and rat cerebral cortical neurons in vitro and in the rat cerebral cortex in vivo. [ 91,92 ]…”
Section: And Apoptosis In the Cnsmentioning
confidence: 99%